2015
DOI: 10.1101/034306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In silicoidentification of metabolic enzyme drug targets inBurkholderia pseudomallei

Abstract: Abstract:The intracellular pathogen Burkholderia pseudomallei, which is endemic to parts of 6 southeast Asia and northern Australia, causes the disease melioidosis. Although acute infections 7 can be treated with antibiotics, melioidosis is difficult to cure, and some patients develop chronic 8 infections or a recrudescence of the disease months or years after treatment of the initial infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 192 publications
(210 reference statements)
1
3
0
Order By: Relevance
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Previous studies have described associations between adaptive metabolism and pathogenesis in intracellular pathogens such as Listeria monocytogenes, Shigella flexneri, Salmonella spp., M. tuberculosis, and B. pseudomallei [37][38][39][40][41][42] ; these findings are consistent with our proteomic results. Arginine deiminase was upregulated in both the passaged B. pseudomallei strain HBPUB15305A and reference strain K96243; this is an enzyme involved in amino-acid metabolism, which may allow passaged B. pseudomallei to use amino acids as an energy source, thus enhancing bacterial survival.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Previous studies have described associations between adaptive metabolism and pathogenesis in intracellular pathogens such as Listeria monocytogenes, Shigella flexneri, Salmonella spp., M. tuberculosis, and B. pseudomallei [37][38][39][40][41][42] ; these findings are consistent with our proteomic results. Arginine deiminase was upregulated in both the passaged B. pseudomallei strain HBPUB15305A and reference strain K96243; this is an enzyme involved in amino-acid metabolism, which may allow passaged B. pseudomallei to use amino acids as an energy source, thus enhancing bacterial survival.…”
Section: Discussionsupporting
confidence: 92%
“…The ability of B. pseudomallei to adapt its metabolic pathways for survival was demonstrated in a previous report 37 . Challacombe et al demonstrated that B. pseudomallei could utilize a wide variety of substrates, including carbohydrates, lipids, glycolipids, dicarboxylic acids, and amino acids during host cell infection.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The transcriptome reveals which genes are expressed/repressed and contribute to the phenotype, allowing inference from the genome landscape (which could be aberrant due to DNA mutations or chromosomal rearrangements) [4]. If the expressed genes encode metabolic enzymes, then such expression levels could directly help to understand an increase in activity of a metabolic pathway and aid in the discovery of drug targets for diseased cells, amenable to pharmacological inhibition [5,6]. Similarly, aberrantly expressed genes which encode non-enzymatic proteins may also be reflective of aberrant metabolism within a diseased cell or sub-cellular niche, albeit indirectly [7].…”
Section: Introductionmentioning
confidence: 99%